Decision making using Neutrosophic And Analytics Hierarchical Process (N-AHP) in choosing the qualified candidate to enter the teacher training institutions / Muhammad Harith Mohamad & Muhamad Husaini Zainol - Mohamad, Muhammad Harith; Zainol, Muhamad Husaini (2019)
Education is the key to success in life and it helps individuals and society to develop socially and economically. The quality of education is assessed through the effective teaching of their teachers. There are two important processes to make sure the quality of teachers which are the recruitment process and the selection process. Therefore, the Neutrosophic and Analytics Hierarchical Process (N-AHP) method, a decision-making instrument was constructed in this project that focuses on the selection process to calculate and to rank the most qualified candidate to enter the teacher training institutions. In this research, four important main criteria and several sub-criteria have been considered, the main criteria which are SPM result, Co-curriculum activities activeness, teacher’s qualification test (UKCG) and physical fitness test (UKF). The weighting of each criterion and sub-criteria were calculated by using the Neutrosophic and Analytics Hierarchical Process (N-AHP) method. The results indicate the ranking of the most qualified candidates to enter the teacher training institution.